SWOT and STP Analysis to Increase Professional Commitment in Participants of the Entrepreneurial Skills Education Program (PKW) at LKP DINA - Rusmaini; Saiful Anwar; Siti Zubaidah; Lodya Sesriyani; Putut Said Permana; Enggar Prasetyawan (Asian Journal of Community Services, 2022)
This PKM aims to increase understanding and mastery of entrepreneurial material for salon business managers as an effort to increase the professional commitment of beauty service business people. Entrepreneurial Skills Education is the implementation of lifelong learning applied at LKP DINA where in its implementation it always partners with the Economic Education study program in relation to how to cultivate an entrepreneurial spirit for activity participants who are in fact novice actors of beauty business ventures. This is in line with the four pillars of learning launched by UNESCO, namely Learning to know, Learning To Do, Learning to Live Together, Learning to Live Together (learning to live together with others in the sense of being able to collaborate and communicate) and Learning to be (learning to be).